Acute Pancreatitis Complicated by Stress Cardiomyopathy With Persistent Apical Akinesis: A Case Report and Literature Review - Temidayo Abe MD; Melvin Simien MD; Hayes Dolphurs MS (Journal of Investigative Medicine High Impact Case Reports, 2019)
Takotsubo cardiomyopathy or stress cardiomyopathy is a transient reversible cardiomyopathy characterized by regional wall motion abnormalities that usually extend beyond a single epicardial vascular distribution. It is often precipitated by acute physical or emotional stressors. In this article, we present the case of a postmenopausal woman who was admitted for management of acute pancreatitis. On the second day of admission, she developed shortness of breath and electrocardiographic abnormalities. A transthoracic echocardiogram revealed left ventricular systolic dysfunction and apical akinesis, and coronary angiography revealed normal coronary arteries. She was diagnosed with takotsubo cardiomyopathy triggered by acute pancreatitis and started on guideline-directed heart failure medications. A follow-up echocardiogram 4 months later revealed persistent systolic dysfunction and apical akinesis.